Theatre Against Oppression: Anti-Colonial Discourse in Late Soviet Uzbek Comedy - Mavlon Bobokhonov (Asiatic: IIUM Journal of English Language and Literature, 2026)
This article examines late Soviet Uzbek comedy as a culturally grounded form of indirect critique, focusing on Said Ahmad’s “The Rebellion of the Brides” (1976) and Sharof Boshbekov’s “The Iron Woman” (1989). Rather than viewing comedy as merely entertaining, the study considers how satire, farce, and grotesque exaggeration created space for expressing tension within a system shaped by ideological control and censorship. Particular attention is given to how domestic life and gender relations become meaningful sites for reflecting broader structures of authority. In The Rebellion of the Brides, the struggle for autonomy within the household points to tensions between centralised control and individual agency. In The Iron Woman, the figure of a mechanical wife highlights the pressures placed on women within the Soviet labour system, especially in the context of rural life and cotton production. In the Uzbek context, such themes are rarely articulated directly. Instead, they emerge through familiar situations and everyday interactions. This suggests that comedic theatre functioned not only as entertainment, but also as a subtle and culturally resonant form of expressing social contradictions.